On constructions of optimal complete diallel crosses - Choi, Kuey Chung; Gupta, Sudhir (Utilitas Mathematica, 2000)
Two general methods of construction leading to several series of universally optimal block designs for complete diallel crosses are provided in this paper. A method of constructing variance balanced designs is also given.